Management in the Field of Cleaning Services Using the Information System - R. Grigoreva, Diana; A. Gareeva, Gulnara (International Journal of Engineering and Technology, 2018)
The cleaning service sector is one of the most promising and fast-growing sectors of the economy. The main goal of the companies is to satisfy the public need for cleaning services for citizens and businesses. The subject of the study is the reengineering of the company's business processes, and in particular the business process "Rendering of cleaning services." As a control system in the enterprise, the MRPII standard is used. MRP are methods of managing an industrial enterprise in a market economy. It provides formation of plans for the provision of services on the basis of a portfolio of orders and forecasting by periods. A preliminary assessment of the service delivery plan for consumers in key needs is in progress. The project aims to design the subsystem "Managing the provision of paid cleaning services" and the development of the task "Accounting for actual volumes of services". The work assesses the managerial and economic effectiveness of the implementation of this task. The presented project can be used for making effective management decisions. The value of reducing the cost of a one-time solution to the business problem "Accounting for actual volumes of services" when implementing and using software is 11,336.55 rub. When solving the problem at the enterprise 12 times a year using the developed software will amount to 136038,6 rub.Â Â